Human Adipose‐Derived Stem Cells Ameliorate Cigarette Smoke‐Induced Murine Myelosuppression via Secretion of TSG‐6. (February 2015) - Xie, Jie; Broxmeyer, Hal E.; Feng, Dongni; Schweitzer, Kelly S.; Yi, Ru; Cook, Todd G.; Chitteti, Brahmananda R.; Barwinska, Daria; Traktuev, Dmitry O.; Van Demark, Mary J.; Justice, Matthew J.; Ou, Xuan; et al.
Abstract Objective: Bone marrow‐derived hematopoietic stem and progenitor cells (HSC/HPC) are critical to homeostasis and tissue repair. The aims of this study were to delineate the myelotoxicity of cigarette smoking (CS) in a murine model, to explore human adipose‐derived stem cells (hASC) as a novel approach to mitigate this toxicity, and to identify key mediating factors for ASC activities. Methods: C57BL/6 mice were exposed to CS with or without i.v. injection of regular or siRNA‐transfected hASC. For in vitro experiments, cigarette smoke extract was used to mimic the toxicity of CS exposure. Analysis of bone marrow HPC was performed both by flow cytometry and colony‐forming unit assays. Results: In this study, we demonstrate that as few as 3 days of CS exposure results in marked cycling arrest and diminished clonogenic capacity of HPC, followed by depletion of phenotypically defined HSC/HPC. Intravenous injection of hASC substantially ameliorated both acute and chronic CS‐induced myelosuppression. This effect was specifically dependent on the anti‐inflammatory factor TSG‐6, which is induced from xenografted hASC, primarily located in the lung and capable of responding to host inflammatory signals. Gene expression analysis within bone marrow HSC/HPC revealed several specific signaling molecules altered by CS and normalized by hASC. Conclusion: Our results suggest that systemic administration of hASC or TSG‐6 may be novel approaches to reverse CS‐induced myelosuppression. Stem Cells2015;33:468–478